Intimacy, sadness-as-courage and post-apartheid disillusionment in Nhlanhla P. Maake’s Mangolo a Nnake - Mochechane, Khumo Sophia (University of the Witwatersrand, Johannesburg, 2024)
In this thesis, I analyse Nhlanhla P. Maake’s 1999 novella, Mangolo a Nnake. While Mangolo readily constitutes apartheid literature, I make a discussion around its prescient nature; that is to say, the ways in which it predicts post-apartheid neocolonialism and ‘ruined time’. The overarching subject matter being black female self-actualisation, I explore Professor Roger Coulibaly’s question, “What do African women need in order to write?”, making a case for the responses space, time and affective prompting. The broad subject of psychosocial support, female solidarity and female social capital is also discussed in line with the ways in which sadness sometimes births the courage to initiate and maintain self-actualisation. By way of close reading of the novella, I discuss various literary devices that are able to cultivate intimacy in a reader. The reader of an epistolary novel can be considered an ‘eavesdropper’, and I show the ways in which literary ‘eavesdropping’ makes way for simulation with a literary character to take place as abstract spectator – that is to say, as reader. I also discuss psychosocial support vis-a-vis female solidarity as an additional need for black women writers. These sometimes find expression by way of storytelling and humour. The latter two are explored in this thesis for their therapeutic and healing abilities. I also read Ntshebo’s disappointment and hurt as allegorical of the larger disappointment of the post-apartheid nation as a result of neocolonialism. A running trope throughout this thesis is the ways in which the concept of the ‘New Woman’ found place and proliferation under the apartheid regime.
A research report Submitted in fulfillment of the requirements for a Master of Arts, In the Faculty of Humanities , School of Literature, Language and Media, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Intimacy; ‘New Woman’; disillusionment; epistolary form; ‘ruined time’; female solidarity; female social capital; self-actualisation; SDG-16: Peace, justice and strong institutions